The effect of various traditional Indonesian face powders on the prevention of UVA and UVB skin pigmentation - Elly Moedijatmini, Elly Moedijatmini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Key words: traditional face powders - sunscreen - UVA - UVB - pigmentation.